Assessment of Microbial Load in Fresh and Frozen Broiler Chicken Samples from Lahore - Muhammad Zubair; Muhammad Ajmal; Nabila Gulzar; Anum Arif (Insights in Animal Science, 2024)
Contaminated chicken meat and its products pose significant hazards to human health. This study was designed to evaluate the quality and microbial safety of fresh and frozen broiler chicken meat samples. A total of 60 samples (30 frozen, obtained from industrially processed sources, and 30 fresh, collected from open vendors) were randomly selected from six locations in Lahore, Punjab, Pakistan. Quality parameters such as pH and color were assessed. The L* value (brightness) was significantly higher in fresh chicken meat (56.64 ± 0.693) compared to frozen meat (44.46 ± 1.456). For a* (red-green coordinate), mean values ranged from 4.6 ± 0.442 to 8.0 ± 0.131 in fresh chicken and 7.6 ± 0.584 to 13.4 ± 0.806 in frozen chicken. Similarly, b* (yellow-blue coordinate) values ranged from 5.6 ± 0.765 to 7.60 ± 0.654 in fresh chicken and 7.2 ± 0.463 to 10.6 ± 0.543 in frozen samples. Microbial analysis revealed the presence of Salmonella spp. and Listeria monocytogenes in fresh samples, while frozen samples tested negative. Fecal coliforms showed optimal growth in frozen samples, but overgrowth was observed in fresh samples. Escherichia coli O157:H7 was absent in frozen samples but detected in fresh samples from three out of five zones. The total bacterial count in frozen chicken remained within safe limits, whereas fresh samples exceeded acceptable levels. Overall, the study concluded that frozen chicken meat is microbiologically safer and of better quality compared to fresh chicken meat.
Keywords: chicken meat; fresh; frozen; meat quality; pH